Stochastic optimized intelligent controller for smart energy efficient buildings - Shaikh, P.H. (Elsevier Ltd, 2014)
Smart buildings are rising concept for energy resource management in the buildings to reduce energy consumption and wastage. Energy management and control system comprises of variety of technologies, which affect human working comfort. The challenging task of the building control is to achieve interior building environment comfort with high-energy efficiency. In this study, multi-agent control system has been developed in combination with stochastic optimization using genetic algorithm (GA). The corresponding simulations of effective management of energy and consumer comfort are presented. The developed control system provides significant improvement in energy consumption and interior environmental comfort in smart buildings. Â© 2014 Elsevier Ltd. All rights reserved.